The Effect of Digital Infographic-Based Project-Based Learning Method on Writing Skill of Descriptive Text - Tetri, Evi Oktavia; Taufiqulloh, Taufiqulloh; Prihatin, Yoga (Journal of English Language and Education, 2025)
This study examines English language skills within the Merdeka Curriculum, focusing on the writing difficulties faced by students, particularly in producing descriptive texts. The methods commonly employed by teachers tend to emphasize reading skills, which negatively impacts writing learning outcomes. This research utilizes a quantitative approach with a factorial experimental design, involving 64 seventh-grade students at SMP Negeri 1 Adiwerna, divided into control and experimental classes. Data were collected through tests assessing students' writing skills in descriptive texts, with variables including the Project-Based Learning (PjBL) method based on digital infographics, writing learning outcomes, and academic achievement. The analysis results indicate significant differences between pre-test and post-test scores, as well as differences in academic achievement between students in low and high categories. There is also an interaction between academic achievement and the teaching method on students' learning outcomes. This study recommends the development of teaching methods that combine conventional elements with PjBL, as well as the need for teacher training in implementing these methods to enhance students' learning outcomes. Further research is also suggested to explore ways to increase student motivation in the learning process.